A LITERATURE REVIEW OF “SANJEEVINI CHOORANAM” IN THE TREATMENT OF ALL TYPE OF POISONOUS SNAKEBITE IN SIDDHA MEDICINE - Mansoor, N.R.; Nithiakumar, N. (University of Jaffna, 2020)
Today the poisonous snake bites are the life threatening problems and significant amount of mortality as morbidity all over the world including Sri Lanka. Snakebite is coming under the Jeeva Nanjukal in toxicology in Siddha Medicine.In the classic snakebite has been considered as difficult to treat due to be difficulty and diagnosis and severity in nature. With these ideas when we searched the Siddha Literatures we found “Sanjeevini Chooranam” for all type of poisonous snakebite. It is mentioned in the book “ruNge;jpu itj;jpa Kiwfs; (tp~ Nuhf rpfpr;ir)” page no 150 – 152. The aim of this study was to literature related review the important characters of Sanjeevini Chooranam which is in the treatment of snakebite. Data were collected from the related authenticated text books and studies in details according to their properties related to Siddha aspect. Collected data had been analyzed according to the organoleptic characters and pharmacological action which enables the chooranam to act on snake bite poisoning. Results and Discussion: The results showed that, among the 49 medicinal plants belonging 21 families were identified and the most common families include Fabaceae, Cucurbitaceae and Apocynaceae and the morphology is 30.6% (15) plants was shrub and 71.4% (35) and 16.3% (8), were used as root bark and bark respectively. These plants contain siddha properties {bitter and sweet taste 56% (28) and 16% (8); hot potency 73.46% (36) and pungent efficacy 79.59% (39)}; pharmacological actions {diuretic 38.3% (36), tonic 37.23% (35), and astringent 35.1% (33)}; 41.49% (39) plants were used as diet and 9.6% (9) were identified as poisonous plants. Conclusion: It is that all the ingredients of the Sanjeevini Chooranam have the property and the pharmacological action to cure for snake bite poisoning. Therefore Sanjeevini chooranam is the best healer for snake bite poisoning. Although this literature review can be provide useful documentation for the management of the snake bite in Siddha Medicine, further extensive scientific studies should be carried out in future.
Keywords: Siddha medicine; Sanjeevini chooranam; Review; Snake bite